2011
DOI: 10.1103/physreve.83.046605
|View full text |Cite
|
Sign up to set email alerts
|

Influence of positional correlations on the propagation of waves in a complex medium with polydisperse resonant scatterers

Abstract: We present experimental results on a model system for studying wave propagation in a complex medium exhibiting low frequency resonances. These experiments enable us to investigate a fundamental question that is relevant for many materials, such as metamaterials, where low-frequency scattering resonances strongly influence the effective medium properties. This question concerns the effect of correlations in the positions of the scatterers on the coupling between their resonances, and hence on wave transport thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Shear moduli for RTV-615 have been reported in Ref. 10 based on a shear wave reflection technique. 29 The following fit is reported for the shear storage (l 0 ) and loss (l 00 ) moduli in the range 30 < f < 500 kHz:…”
Section: B Sample Fabrication and Acoustic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear moduli for RTV-615 have been reported in Ref. 10 based on a shear wave reflection technique. 29 The following fit is reported for the shear storage (l 0 ) and loss (l 00 ) moduli in the range 30 < f < 500 kHz:…”
Section: B Sample Fabrication and Acoustic Measurementsmentioning
confidence: 99%
“…7 There has been renewed interest in monopole resonant scattering in soft media for experimental studies of phononic crystals and phenomena associated with random distributions of scatterers. [8][9][10] The influence of cavity shape on natural frequency was studied in Meyer et al 6 where a variety of shapes molded into rubber were examined experimentally. Deviations from spherical predictions were noticed for large aspect ratio (AR) shapes as also found in Ivansson. 11 Recent numerical work 12 has shown that the monopole resonance frequency of an evacuated sphere in a soft medium can be reduced by a factor of up to 6 by distorting the shape into a high AR oblate spheroid keeping the volume constant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since focusing techniques are often used in NDE applications, it would be of interest to study the response from a small focal region containing cavities, rather than a layer. Correlations in scatterer locations were also not considered in the present study, although some work exists on the effect of such correlations on the expected response, 12 and this could be a further relevant area for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The field is still an active one, despite its long history, and although many works are based on elastostatic analyses 9,10 rather than on wave propagation, new variants on effective medium models are published frequently. 11,12 Let us consider what this coherent field is, and whether it is indeed what is actually measured in an experimental system. Foldy 13 states that although the scattered fields are all coherent, the resultant field is separated into that part termed (and now known as) the coherent field which propagates uniformly and other scattered components referred to as incoherent scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Correct wave equations are thereby essential for a sufficient understanding of the physics governing the wave behavior. A number of theoretical studies have intensively been performed (Kuznetsov et al, 1978;Commander and Prosperetti, 1989;Nigmatulin, 1991;Gumerov, 1992;Nakoryakov et al, 1993;Akhatov et al, 1996;Khismatullin and Akhatov, 2001;Liang et al, 2008;Vanhille and Campos-Pozuelo, 2009;Ando et al, 2011;Leroy et al, 2011;Grandjean et al, 2012;Louisnard, 2012;Sinelshchikov, 2013, 2014, to name a few), and various nonlinear wave equations describing weakly nonlinear phenomena were submitted. The KdVB equation (e.g., van Wijngaarden, 1968van Wijngaarden, , 1972 and the nonlinear Schr€ odinger (NLS) equation (e.g., Gumerov, 1992;Akhatov et al, 1996) are two well-known nonlinear equations for plane waves in uniform bubbly liquids.…”
Section: Introductionmentioning
confidence: 99%